Stillwater and Koo save the world - Muth, Jon J. (Untitled zen younger picture book, 2023)
Stillwater the giant panda's nephew, Koo, has a dream about saving the world, and Stillwater shows him that sometimes saving the world starts with doing the little things, like cleaning your room, and feeding the cat.